Sosialisasi Pengolahan Tanah untuk Budidaya Tanaman Nanas di Harum Manis - Andri Andri; Leony Agustine; Grin Tommy Panggabean (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2024)
Pineapple plants are one of the leading fruits that have high economic potential in Indonesia, but often pineapple cultivation is not optimal, especially in terms of land management. The implementation of this PKM aims to provide socialization on correct soil processing to pineapple farmers in Harum Manis, Kubu Raya Regency. Pineapple farmers in that location still don't understand how to cultivate the land properly and just plant like that. Moreover, there are many obstacles currently faced by farmers, such as land shortages and extreme climate change. The method used in implementing this PKM is direct socialization followed by questions and answers. The activity went very well as shown by the enthusiasm of the farmers participating in this activity. It is hoped that after this PKM activity is completed, pineapple farmers can carry out proper soil processing to increase optimal pineapple growth and production.